The Effect of Career Planning, Compensation, and Climate on OCB, Mediated by Pos, at Bappenas - Rudolf, Frejon; Riyanto, Setyo (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study analyzes Organizational Citizenship Behavior (OCB) as voluntary behavior of employees that exceeds formal job requirements among Non-Civil Servant Government Employees (PPNPN) at the Ministry of National Development Planning/National Development Planning Agency (PPN/Bappenas). The importance of this study is driven by the strategic role of PPNPN in policy formulation and national development planning; however, their non-civil servant status may influence voluntary work behavior, which is critical for organizational effectiveness. The research was conducted in 2025 with a population of 1,088 PPNPN and used a purposive sample of 190 PPNPN with a Master's degree (S2). The research method employed a quantitative approach with a causal design, data collection through a structured 5-point Likert scale questionnaire, and Structural Equation Modeling (SEM) analysis using SmartPLS 4.0 software to test the influence of Career Planning, Compensation, and Organization Climate on OCB with Perceived Organizational Support (POS) as a mediator. The results of the study indicate that Career Planning (t=8.569; p=0.000), Compensation (t=1.985; p=0.020), and Organization Climate (t=2.665; p=0.004) have a significant positive effect on OCB. POS was found to be effective in partially mediating this relationship, although Career Planning does not directly influence POS, it can still influence OCB through POS mediation with an R² value of 0.617, explaining 61.7% of the variation in OCB